STUDI FAKTOR PENENTU PEMBELIAN ULANG PADA RESTORAN A&W DI KOTA SEMARANG - Ihsan Saputra, Muhammad Rio; Rahardjo, Susilo Toto (Diponegoro Journal of Management, 2024)
ABSTRACT This study focuses on the relationship between service quality, price fairness, and viral marketing as factors that influence repurchase intention, with customer experience as a mediating variable. Semarang City, as one of Indonesia's largest cities and a tourist destination, provides a significant backdrop for this study. With high tourist attraction and surging interest in fast food in Indonesia, particularly in Semarang City, fast food restaurants such as A&W have great potential to understand and increase customer repurchase intention. This study involved 150 respondents who were selected using the Non-Probability Sampling method by Purposive Sampling. Data Analysis Technique Structural Equation Model (SEM) with Analysis of Moment Structure (AMOS) 24 program was used to analyze and interpret the relationship between variables. The criteria for research respondents are customers who have visited A&W restaurants in Semarang City at least once. The results of the research hypothesis show that service quality, price fairness, and viral marketing positively and significantly affect repurchase intention. Service quality has the strongest influence on repurchase intention, followed by price fairness, and e-WOM with the least influence. These findings provide valuable insights for A&W restaurant management to develop more effective strategies to increase customer repurchase intention, by focusing attention on improving service quality, fair pricing policies, and creative viral marketing